Zoonotic Staphylococcus spp. among domestic animals in Ukraine: antibiotic resistance and diagnostic approaches - Shevchenko, M.; Andriichuk, A.; Naumchuk, V.; Petruk, I.; Bilyk, S.; Tsarenko, T. (Regulatory Mechanisms in Biosystems, 2023)
Staphylococcus pseudintermedius and S. aureus are common infectious agents with zoonotic potential, capable of acquiring antibiotic resistance and causing hospital-acquired infections. This study aimed to assess the prevalence of S. pseudintermedius among dogs in Ukraine and explore the possibility of using chromogenic media for accurate identification and differentiation of S. aureus and S. pseudintermedius. The data obtained indicate a higher prevalence of nasal carriage (44.8%) of Staphylococcus spp. in healthy dogs compared to ear carriage (28.5%). Among the isolated strains in nasal swabs, S. pseudintermedius was most often detected (24.1%), S. aureus was detected less often (5.2%). Among the samples taken from sick dogs, 36.5% were found to be Staphylococcus spp., of which 20.5% contained S. pseudintermedius and 4.5% S. aureus. Among the studied cats, 36.8% were found to contain Staphylococcus spp., S. pseudintermedius – 10.5%, and S. aureus – 5.3%. Antibiotic resistance profiles were different: S. pseudintermedius was resistant to the combination of trimethoprim-sulfamethoxazole, as well as to penicillin and erythromycin, while S. aureus was resistant to penicillin. It should be noted that only one coagulase-positive S. aureus isolate obtained from healthy animals was resistant to oxacillin. The use of chromogenic media demonstrated the possibility of successful differentiation of S. aureus and S. pseudintermedius based on differences in culture properties. In addition, various combinations of microbiological tests were evaluated, resulting in the development of two schemes that included specific media and additional reactions to improve identification accuracy. The combination of CHROMagar™ Orientation with the coagulase detection reaction demonstrated higher sensitivity (100%) for the detection of S. pseudintermedius compared to the combination of mannitol salt agar (MSA) with the coagulase detection reaction (75%). In addition, the PCR reaction was valuable for the definitive identification of coagulase-positive staphylococci (CoPS). These comprehensive results shed light on the prevalence, species distribution, antibiotic resistance patterns, and diagnostic approaches for S. aureus in dogs and cats in Ukraine, emphasizing the importance of developing reliable surveillance and control strategies.